How far corporate governance and firms' characteristics are relevant toward environmental sustainability? An empirical investigation - Suchismita Ghosh; Ritu Pareek; Tarak Nath Sahu (Rajagiri Management Journal (RAMJ), 2023)
Purpose - The study aims to focus to ascertain the consequence of corporate management and different firms' characteristics on environmental sustainability. Design/methodology/approach - The sample includes 78 non-financial NSE 100 listed companies from 2010 to 2020. Here, the static and Arellano-Bond dynamic panel data model is considered to determine the effect of corporate governance mechanisms and different firms' characteristics on environmental performance. Findings - The empirical findings of this study indicate that board size is negatively related with environmental sustainability. Similarly a positive influence of age, size and market-based financial performance can be seen on sustainability of the firm. Originality/value - The present study takes an initiative to determine endogeneity and the dynamism effect of corporate governance factors and specific firms' characteristics on environmental sustainability from an emergent nation.
Keywords: 650; Corporate governance; Firms'characteristics; Environmental sustainability; Panel data analysis